Interleukin-36α axis is modulated in patients with primary Sjögren's syndrome. (3rd June 2015) - Ciccia, F; Accardo-Palumbo, A; Alessandro, R; Alessandri, C; Priori, R; Guggino, G; Raimondo, S; Carubbi, F; Valesini, G; Giacomelli, R; Rizzo, A; Triolo, G
Summary: The aim of this study was to investigate the expression of the interleukin (IL)-36 axis in patients with primary Sjögren's syndrome (pSS). Blood and minor labial salivary glands (MSG) biopsies were obtained from 35 pSS and 20 non-Sjögren's syndrome patients (nSS) patients. Serum IL-36α was assayed by enzyme-linked immunosorbent assay (ELISA). IL-36α, IL-36R, IL-36RA, IL-38, IL-22, IL-17, IL-23p19 and expression in MSGs was assessed by reverse transcription–polymerase chain reaction (RT–PCR), and tissue IL-36α and IL-38 expression was also investigated by immunohistochemistry (IHC). αβ and γδ T cells and CD68 + cells isolated from MSGs were also studied by flow cytometry and confocal microscopy analysis. IL-36α was over-expressed significantly in the serum and in the salivary glands of pSS. Salivary gland IL-36α expression was correlated with the expression levels of IL-17, IL-22 and IL-23p19. IL-38, that acts as inhibitor of IL-36α, was also up-regulated in pSS. αβ + CD3 + T cells and CD68 + cells were the major source of IL-36α in minor salivary glands of pSS. γδ T cells were not significantly expanded in the salivary glands of pSS but produced more IL-17, as their percentage correlated with the focus score. Higher expression of IL-36α and IL-36R was also demonstrated in γδ T cells isolated from pSS compared to controls. In this study we demonstrate that a significant increase in circulating and tissue levels of IL-36α occurs in pSS patients.